The impact of zerovalent cobalt nanoparticle on photosynthesis - related genes expression in soybean leaves Glycine max (L.) Merr. (Dt26) - Tam, Luu Thi; Hien, Hoang Thi Minh; Anh, Hoang Thi Lan; Tuan, Phan Hoang; Hong, Dang Diem (Academia Journal of Biology, 2019)
Photosynthesis is an important physiological process in plants. It plays a crucial role in plant growth and development. In this study, we investigated the impact of zerovalent cobalt nanoparticles on the photosynthesis and expressing of gene involving in this process in leave of soybean Glycine max (L) Merr “DT26” at different growth stages. The results showed that treatment of zerovalent cobalt nanoparticles made in Vietnam and USA (with two doses of 0.17 and 16.67 mg/kg of soybean seed) enhanced the photosynthesis of soybean by increasing the content of chlorophyll a and the ratio of Fv/Fm compared with the control (without treatment of zerovalent cobalt nanoparticles). These values tended to increase and reached the maximum value at 40 days and then decreased in at 70 days. The expression level of photosynthesis-related genes of soybean leaves also changed depending on the soybean’s growth stage and concentration of zerovalent cobalt nanoparticles being treated. The genes psaA, Lhca, psaB, Cytb6f (belonging to photosystem I) and psbA, psbB, psbC, psbD, psbE (belonging to photosystem II) in the experimental fomulas were higher expressed than that in control group at 20 and 70 days. However, at 40 days, the expression levels of these genes were significantly different. Obtained results supplied the basis for understanding the active mechanism of the above genes to control/regulates photosynthetic activity of plants with and without the presence of zerovalent cobalt nanoparticles as well as under stress conditions.